Systematic Foliar Anatomy in Nine Strobilanthes Blume Species (Acanthaceae) from Kerala, India - PATIL, A.M.; D.A. PATIL (Research Perspective on Biological Science Vol. 1, 2025)
Strobilanthesis Blume acanthaceous a genus with about 200 species and is distributed mostly in Asia. They are either shrubs or herbs with often opposite leaves. Only a limited number of species have been investigated anatomically, particularly for foliar structure. Therefore, the author attempted to reveal anatomical features of foliage leaves in nine species of the genus Strobilanthes Blume (Acanthaceae), collected from different locations in Kerala. Leaves of all the collected plants are bifacial. The features such as resolution of vascular tissue in midrib region, occurrence of sclerenchyma, collenchyma, layers of palisade, cystoliths, sphaeraphides, etc. differ from taxon to taxon and are found systematically significant. They are employed in devising an artificially dichotomous key as an aid in their identification. Extended observations were made on the selected species of the genus, contributing to a deeper understanding of their foliar anatomy within the family Acanthaceae. These findings are presented with particular emphasis on their systematic value.